Innovation adoption in the agri-food system: a model proposition - Ribeiro, Marcela Naves Costa (2023)
The agrifood system is of great economic importance, providing a significant contribution to countries\' gross domestic product (GDP), and is responsible for feeding an ever-growing population, even in the face of challenges related to natural resource scarcity and climate change. These challenges mean that the sector has significant potential for innovation development and adoption. One of the great innovations in the agrifood system is alternative protein, a product capable of replicating the taste, texture and appearance of meat, but derived from vegetables, plants and other non-conventional sources. Innovation adoption occurs when an organization chooses to adopt an innovation, whether through new products, processes, systems, or other means, generated internally or externally acquired. The literature on the subject presents innovation adoption models that provide an efficient and structured way to analyze innovation adoption. However, studies dealing with adoption models in the agrifood system are scarce. Therefore, the objective of this thesis is to propose a model of innovation adoption for the agrifood system that can identify the constituent elements of adoption and facilitate its implementation in the sector. To achieve this objective, the thesis is divided into 3 articles. Article 1 aimed to identify the main innovations that are adopted in the agrifood system, through a systematic literature review. The purpose of article 2 was to identify the perceptions of innovation characteristics that may influence innovation adoption, and article 3 aimed to analyze the influence of external variables and internal characteristics on innovation adoption. Articles 2 and 3 used semi-structured interviews with managers involved in the process of innovation adoption in the agrifood system in Brazil and content analysis and thematic analysis was used to analyze the data. At the end of the thesis is proposed an innovation adoption model for the agrifood system, which takes into account the perceived characteristics of the innovation, the influence of external variables and also its internal characteristics. The model is a valid contribution between the needs of the scientific community and the needs of the market, as it provides an organized and structured approach to guide the innovation adoption and it permits to analyze the influence of the different dimensions that most affect agrifood system organizations in the adoption process.